Thoracic Duct Cannulation and the Course of Toxemia in Peritonitis (an Experimental Study) - V. I. Karandin; A. G. Rozhkov; M. I. Tsarev; R. M. Nagayev; P. A. Tikhonov (Общая реаниматология)
Objective: to study the mechanisms of redistribution of toxins between biological media (blood and lymph) during enhanced lymph circulation after thoracic duct cannulation. Materials and methods. Experimental studies were performed on 12 mongrel dogs with reproduced general purulent peritonitis, which were divided into 3 groups and which differed in various times of thoracic duct cannula functioning. The redistribution of toxins was based on the study of medium-weight molecular fractions in different development periods of endotoxicosis. Results. Clinical observations have ascertained and confirmed that the potentiated draining effect of the lymphatic system in surgical endotoxicosis depends on the completeness of lymph circulation rearrangement after thoracic duct cannulation and external lymph drainage restoration. Conclusion. It is expedient to carry out thoracic duct cannulation as soon as possible if the course of surgical endotoxico-sis is supposed to be severe. This will accelerate lymph circulation rearrangement and ensure a prompter elimination of toxins, which can enhance the efficiency of extracorporeal lymph detoxification. Key words: lymph circulation, endotoxicosis, thoracic duct cannulation, medium-weight molecules.